2018
DOI: 10.3389/fcvm.2018.00097
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Macrophages: Understanding Mechanisms of Activation as Guide to Therapy for Atherosclerotic Vascular Disease

Abstract: An emerging theory is that macrophages are heterogenous; an attribute that allows them to change behavior and execute specific functions in disease processes. This review aims to describe the current understanding on factors that govern their phenotypic changes, and provide insights for intervention beyond managing classical risk factors. Evidence suggests that metabolic reprogramming of macrophages triggers either a pro-inflammatory, anti-inflammatory or pro-resolving behavior. Dynamic changes in bioenergetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 133 publications
0
24
0
Order By: Relevance
“…Evidence established that macrophages are a heterogeneous group of cells, as represented by the well-known theory of M1 versus M2 polarization. Recent understanding, however, suggests that macrophage heterogeneity is more complex and multidimensional than the M1/M2 dichotomy (Murray et al 2014;Nahrendorf and Swirski 2016;Decano and Aikawa 2018). In our study, single-cell analysis demonstrated that IFNγ-elicited macrophages remain largely heterogeneous, consisting of a few clusters rather than uniformly "polarized" toward an activated phenotype (Iwata et al 2016).…”
Section: Parp9 and Parp14 Regulate Macrophage Activationmentioning
confidence: 47%
See 1 more Smart Citation
“…Evidence established that macrophages are a heterogeneous group of cells, as represented by the well-known theory of M1 versus M2 polarization. Recent understanding, however, suggests that macrophage heterogeneity is more complex and multidimensional than the M1/M2 dichotomy (Murray et al 2014;Nahrendorf and Swirski 2016;Decano and Aikawa 2018). In our study, single-cell analysis demonstrated that IFNγ-elicited macrophages remain largely heterogeneous, consisting of a few clusters rather than uniformly "polarized" toward an activated phenotype (Iwata et al 2016).…”
Section: Parp9 and Parp14 Regulate Macrophage Activationmentioning
confidence: 47%
“…Overwhelming evidence has associated chronic inflammation with various pathological conditions and their potential causes, including atherosclerosis, cardiovascular events, cancer, autoimmune diseases, metabolic disorders, neurological diseases, and aging (Johnston et al 1987;Gisterå and Hansson 2017;Tabas and Lichtman 2017;de Vries and Quax 2018;Gomez et al 2018;Aday and Ridker 2019;Bercovici et al 2019;Di Benedetto et al 2019;Guner and Kim 2019;Horwitz et al 2019;O'Rourke et al 2019;Othman et al 2019;Trott and Fadel 2019). Many investigations have focused on the major role of macrophages in such contexts and mechanisms for their proinflammatory activation (Murray and Wynn 2011;Wynn and Vannella 2016;Gisterå and Hansson 2017;Tabas and Lichtman 2017;Decano and Aikawa 2018;Funes et al 2018;Swirski and Nahrendorf 2018;O'Rourke et al 2019). Various signal-transduction pathways participate in macrophage activation, which are often regulated by PTMs such as phosphorylation and acetylation (Tietzel and Mosser 2002;Park et al 2011;Zhou et al 2014;Nakano et al 2016;Vergadi et al 2017;Dean et al 2019).…”
Section: Parps In Immune Cells: a Focus On Inflammationmentioning
confidence: 99%
“…Recently, M s have been reported to play an essential role in tissue development and homeostasis through increased angiogenesis and vascular remodeling (1,4,5). M s also have attracted significant interest in human diseases as they play crucial roles in many diseases associated with chronic inflammation such as atherosclerosis, obesity, diabetes, cancer, skin diseases, and neurodegenerative diseases (6,7). Implantation is a vital process of the first feto-maternal encounter in the uterus, leading to pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy immune response during infection or injury is a dynamic process consisting of initial, acute pro-inflammatory activation followed by anti-inflammatory/resolving activity, which is mediated in large part by macrophages 1,2 . This temporally regulated response promotes pathogen and debris clearance followed by tissue regeneration and, ultimately, recovery of homeostasis ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This temporally regulated response promotes pathogen and debris clearance followed by tissue regeneration and, ultimately, recovery of homeostasis ( Fig. 1a) 1,2 . Dysregulation can occur in several ways.…”
Section: Introductionmentioning
confidence: 99%